1983
DOI: 10.1007/bf01401431
|View full text |Cite
|
Sign up to set email alerts
|

Arterio-venous epidural shunting in epidural bleeding radiological and physiological characteristics. An experimental study in dogs

Abstract: In order to test the possibility suggested in previous studies that the long bleeding time and the large bleeding volume observed in experimental epidural bleeding can be explained by the development of an arterio-venous shunt, water soluble X-ray contrast was injected into the epidural space in dogs during an epidural bleeding in progress. It was found that the contrast medium left the epidural space through diploic veins in the cranial bone to the neck veins. By draining off epidural blood the arterio-venous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…1. They are similar to results reported previously 11,12,16,26,41. In short the bleeding rate and haematoma volume increase was rapid at first and then slowed gradually.…”
Section: Intracranial Bleeding and The Course Of Intracranial Pressuressupporting
confidence: 92%
See 2 more Smart Citations
“…1. They are similar to results reported previously 11,12,16,26,41. In short the bleeding rate and haematoma volume increase was rapid at first and then slowed gradually.…”
Section: Intracranial Bleeding and The Course Of Intracranial Pressuressupporting
confidence: 92%
“…Blood gas measurements were taken immediately after each CBF measurement. Each animal served as its own control, according to a protocol previously described in several studies from this laboratory 11,12,16,35,36,41,42 The physiological changes observed during these experiments were not affected by changes in blood gases. The mean values for the 3 groups are shown in Table 1.…”
Section: Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no abnormalities of PaO 2 PaCO2 or arterial pH in any of the groups and no significant difference between groups. Each animal was observed for 10 to 30 minutes after completion of the preparation, and in the case of spontaneously breathing animals following disconnection of the ventilator, according to a protocol used in many previous studies 9, 13,25,35,37,38 No systematic change occurred in any variable during this period.…”
Section: Control Testsmentioning
confidence: 99%
“…1 illustrates an experiment in a cat with an intracranial volume of 24.0 ml. The rate of balloon expansion was 1.00ml/minute, i.e., 4.17% of intracranial volume per minute. After the start of inflation, blood pressure, respiration and heart rate remained unchanged until the balloon volume had reached a size of 1.05 ml (4.4% of intracranial volume), when arterial pressure started to rise and the respiration frequency to diminish.…”
Section: Cats Group Imentioning
confidence: 99%